If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-66+6n=-6(11-13n)
We move all terms to the left:
-66+6n-(-6(11-13n))=0
We add all the numbers together, and all the variables
6n-(-6(-13n+11))-66=0
We calculate terms in parentheses: -(-6(-13n+11)), so:We get rid of parentheses
-6(-13n+11)
We multiply parentheses
78n-66
Back to the equation:
-(78n-66)
6n-78n+66-66=0
We add all the numbers together, and all the variables
-72n=0
n=0/-72
n=0
| 4x^2=x+93 | | 7x+8=-7x+120 | | 55(x-8)+44(x+5)=220*6+20(x+2) | | 6−2h=4 | | -5r-6r=-22 | | 5(2a-3)=13a-3(a-5) | | 144+3x^2=324 | | -2x+9+7x=-1 | | 9w+3=2(w+5) | | 5^(x-1)-7^(2-2x)=0 | | z÷8-2=1 | | 2(4w-3)=-2(2w+15) | | 5v-8v=-18 | | 5x-7/3=x+9/4 | | (x-8/4)+(x+5/5)=6+(x+2/11) | | X/x-3=6/10 | | -9v+21=-4(v-9) | | 5(-3)+2y=-7 | | 8+x+3x=180 | | 30000((0.65x-32500)-300000)=15000(0.65x-107250) | | 8x^2-65x-63=(5x+3) | | 2((0.65x-32500)-300000)=(0.65x-107250) | | 3x-2.6=x+9.2 | | 4=y/8+1 | | 2x+17=16-4 | | 4x-3=x+10 | | −6/t−7=17 | | 4b+5=13 | | (5x-66)-30=(5x-66) | | -3(3)+y=15 | | X^2+x+7=19 | | 6x=2x^2/3 |